Pengaruh Beban Kerja, Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan : Studi PT. Erafone Artha Retailindo Cabang Serang - Susanti, Weni; Tarmizi, Achmad (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
Each company will select prospective employees who meet the qualifications determined by the company. This aims to get quality employees so they can carry out organizational tasks so that company goals can be achieved. Therefore, employee performance is a must to achieve organizational performance. The aim of this research is to determine the influence of workload, organizational culture and work environment on employee performance at PT. Erafone Artha Retailindo Serang Branch. This research is quantitative research. The population of this research is employees of PT. Erafone Artha Retailindo Serang Branch and sampling technique with a saturated sample of 50 respondents. Data collection method by distributing questionnaires. Data analysis methods use validity tests, reliability tests, normality tests, multicollinearity tests, autocorrelation tests, heteroscedasticity tests, coefficient of determination tests and t tests. The results of this research conclude that workload does not have a significant effect on employee performance. Meanwhile, organizational culture and work environment have a significant influence.